Near-Newtonian Blood Behavior – Is It Good to Be a Camel? - Windberger, Ursula; Auer, Roland; Seltenhammer, Monika; Mach, Georg; Skidmore, Julian A. (Frontiers in Physiology, 2019)
From a certain level of exercise-intensity onwards, hematocrit increases in horses, which brings more oxygen carriers into the bloodstream. Camels, however, when used in competitive racing could be even in need of iron supplementation and blood transfusions due to a severe reduction of their available hematocrit compared to their resting hematocrit. Since the extrinsic and intrinsic mechanical properties of camel erythrocytes (RBC) are so different compared to RBCs of other mammals, the question arises whether this observation might be a response to endurance exercise aiming at keeping the RBC count low. Rheometry indicated dromedary camel blood to behave almost Newtonian, which is unique amongst mammals. Shear thinning did increase with the hematocrit, but remained marginal compared to horses. As a result, camel whole blood viscosity (WBV) exceeded horse WBV at high shear rates, an effect, which was significantly augmented when the packed cell volume (PCV) was increased. Therefore, in camels any infusion of RBCs into the bloodstream can increase the cardiac work and the energy input into the endothelium more effectively, which should generate vascular remodeling in the long term. Yielding, however, was completely absent in camel blood, even at PCVs above 70%, confirming low cohesion between its components at quasi-static flow condition. Camel blood remained a viscous liquid without a threshold even at unphysiologically high PCVs. This can help to washout lactate when camels start to dehydrate and might contribute to the sustained working ability of these animals. The subtle pseudoplastic behavior and the high viscosity contrast across the RBC membrane point to weak coupling between blood flow and red cell behavior. We predict that RBCs flow as separate entities and can show various types of motion, which can lead to friction instead of being collectively aligned to the flow direction. In comparison to horses, this behavior will become clinically relevant at higher RBC counts in front of flow obstacles and possibly cause vascular remodeling.